2004
DOI: 10.1111/j.1600-0047.2004.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mental health services in Europe: results from the European Study of the Epidemiology of Mental Disorders (ESEMeD) project

Abstract: The ESEMeD results suggest that the use of health services is limited among individuals with mental disorders in the European countries studied. The factors associated with this limited access and their implications deserve further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
141
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(161 citation statements)
references
References 17 publications
16
141
0
4
Order By: Relevance
“…This finding is consistent with previous studies that found that gender is a predicting factor of service use [1][2][3] . When assessing hospital admissions, the second objective, we found some interesting results: men have a higher risk of a first hospitalisation and, in addition, the length of admissions is longer for them.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with previous studies that found that gender is a predicting factor of service use [1][2][3] . When assessing hospital admissions, the second objective, we found some interesting results: men have a higher risk of a first hospitalisation and, in addition, the length of admissions is longer for them.…”
Section: Discussionsupporting
confidence: 83%
“…The fact of being a woman has repeatedly proved to be a predicting factor of higher service use [1][2][3] . Studies on prevalence in the general population show that women have twice the risk of suffering mood disorders-especially dysthymia-throughout their lives [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of treatment seeking report that somewhere between 36.5 and 50 % of individuals with depression actually seek professional help [21,22]. This indicates that even though the participants in the present study had recent contact with psychiatric health care this did not seem to facilitate renewed contact with a professional.…”
Section: Status Of Depression At 12-month Follow-upmentioning
confidence: 52%
“…Therefore, an early detection and adequate intervention are crucial to reduce overall burden and disability associated with neuropsychiatric disorders [7]. One important reason for the duration of untreated illness is that more than a third of patients with a psychiatric disorder do not or only with delay seek help from a mental health professional [8]. In contrast, most children and adolescents are regularly seen by general medical professionals for other reasons (e.g., primary care physician, pediatrician, or nurse) and/or by school counselors (pedagogues, social workers, or sometimes psychologists) if they have behavioral or emotional problems.…”
Section: Introductionmentioning
confidence: 99%